Effect of budesonide/formoterol pressurized metered-dose inhaler on exacerbations versus formoterol in chronic obstructive pulmonary disease: The 6-month, randomized RISE (Revealing the Impact of Symbicort in reducing Exacerbations in COPD) study. (November 2017) - Ferguson, Gary T.; Tashkin, Donald P.; Skärby, Tor; Jorup, Carin; Sandin, Kristina; Greenwood, Michael; Pemberton, Kristine; Trudo, Frank
Abstract: Background: Prevention of exacerbations is a primary goal for chronic obstructive pulmonary disease (COPD) therapy. This randomized, double-blind, double-dummy, parallel-group, multicenter study evaluated the effect of budesonide/formoterol pressurized metered-dose inhaler (pMDI) versus formoterol dry powder inhaler (DPI) on reducing COPD exacerbations. Methods: 1219 patients aged ≥40 years with moderate-to-very-severe COPD (per lung function) and a history of ≥1 COPD exacerbation received budesonide/formoterol pMDI 320/9 μg twice daily (BID) during a 4-week run-in. Patients were then randomized 1:1 to receive budesonide/formoterol pMDI 320/9 μg BID (n = 606) or formoterol DPI 9 μg BID (n = 613) for 26 weeks. Exacerbations were identified using predefined criteria for symptom worsening and treatment with systemic corticosteroids and/or antibiotics and/or hospitalization. The primary endpoint was annual rate of exacerbations. Results: Budesonide/formoterol pMDI resulted in a 24% reduction in annual rate of exacerbations (0.85 vs 1.12; rate ratio: 0.76 [95% CI: 0.62, 0.92]; P  = 0.006), and a significant risk reduction for time to first exacerbation (hazard ratio: 0.78 [95% CI: 0.64, 0.96]; P  = 0.016) versus formoterol DPI. The most commonly reported adverse events (AEs; ≥3%) in budesonide/formoterol and formoterol groups were COPD (4.5% vs 8.6%) and nasopharyngitis (5.0% vs 5.2%). Pneumonia AEs were reported in 0.5% and 1.0% of budesonide/formoterol-treated and formoterol-treated patients, respectively. Conclusions: Budesonide/formoterol pMDI is an effective treatment option for reducing exacerbation rates in COPD patients with moderate-to-very-severe airflow limitation and history of exacerbations. No increase in pneumonia was observed with budesonide/formoterol; safety data were consistent with its established profile. Highlights: Chronic obstructive pulmonary disease (COPD) therapy aims to prevent exacerbations. RISE evaluated the impact of BUD/FM pMDI on reducing the rate of COPD exacerbations. BUD/FM pMDI significantly reduced the annual exacerbation rate by 24% vs FM alone. Safety data were consistent with the established profile of BUD/FM pMDI. BUD/FM pMDI is an effective treatment option for preventing COPD exacerbations.